Анатомо-гистологическое строение ротовой полости афалины (Tursiops truneatus М.) - Гилевич, С.А.; Луханин, В.Я. (Вестник зоологии, 1981)
The paper deals with data on anatomy andhistology of the mouth cavity walls (lips, cheecks palate, bottom), teeth and tongue of Tursiops truncatus, M. Peculiarities ol their structure related to the properties of these organs functioning are stated. Absence of a chewing functioncaused disappearance of lips muscles, involution of the check muscle and also aflected the structure and arrangement of teeth and tongue structure. Morphofunctional transformations of the mouth cavity organs in dolphins under study resulted in general from food and hydrodynamic factors.